PENGARUH KETERAMPILAN MANAJERIAL KEPALA SEKOLAH TERHADAP KEPUASAN KERJA GURU DI SEKOLAH DASAR - Nada Shofa Lubis; Desy Safitri; Didik Iskandar (STKIP Pesisir Selatan, 2026)
This study aims to analyze the effect of principals’ managerial skills on teachers’ job satisfaction in elementary schools. The study was grounded in the strategic role of principals in developing effective, communicative, and supportive school governance for teachers. A quantitative approach with an explanatory correlational design was employed. The research was conducted at SDN Bugel 02 Kota Tangerang, involving 30 teachers selected through saturated sampling. Data were collected using a closed-ended Likert-scale questionnaire and analyzed through Partial Least Squares Structural Equation Modeling using SmartPLS. The findings reveal that principals’ managerial skills have a positive and significant effect on teachers’ job satisfaction, as indicated by a path coefficient of 0.817, t-statistics of 15.689, and p-values of 0.000. The R Square value of 0.667 indicates that principals’ managerial skills explain 66.7% of the variation in teachers’ job satisfaction. These findings emphasize that planning, coordination, communication, supervision, and professional guidance are essential managerial practices for creating a conducive, professional, and sustainable work environment that meaningfully strengthens teachers’ satisfaction in public elementary schools today.